WELDING QUALITY CONTROL USING THE FAILURE MODES AND EFFECTS ANALYSIS (FMEA) METHOD AT PT. X - M.Raja Shafa Aulia Jalal Jalal; Adi Kurniawan Yusim (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2024)
This research aims to identify and analyze defects in the welding process at PT. X uses the FMEA method. The primary defects found were cracks, porosity, spatter, and undercut. The leading causes of crack defects are poor material conditions, porosity caused by inadequate facilities, spatter due to inappropriate parameter settings, and undercut due to lack of supervision. The highest RPN value is crack, with a score of 288, followed by porosity (280), spatter (196), and undercut (175), indicating that crack and porosity require special attention. Improvement strategies include improving material quality and inspection procedures for cracks, improving facilities for porosity, operator training and automated monitoring for spatter, and increased monitoring for undercuts. Based on the visualization of the Pareto diagram, the number of defects that frequently occurred was spatter in 16 cases with a percentage of 36%, followed by undercut in 11 cases (25%), crack in 9 cases (21%), and porosity in 8 cases (18%). This data was collected from production that experienced defects from January – April 2024. The Pareto diagram shows that spatter is the most frequently occurring defect, even though it has a lower RPN than crack and porosity. Therefore, the repair priority must remain on crack and porosity because of their significant impact on weld quality. Implementing the proposed improvement strategy is expected to reduce the risk of failure and increase the efficiency and quality of the welding process at PT. X.